2004
DOI: 10.1086/381942
|View full text |Cite
|
Sign up to set email alerts
|

The Synergistic Effects of Stochasticity and Dispersal on Population Densities

Abstract: Using laboratory experiments, simulation models, and analytical techniques, we examined the impact of dispersal on the mean densities of patchily distributed populations. Even when dispersal leads to no net additions or removals of individuals from a population, it may nonetheless increase mean population densities if the net immigration rate is positive when populations are growing and negative when they are declining. As a model system for exploring this phenomenon, we used the yeastlike fungus Aureobasidium… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
54
3
6

Year Published

2006
2006
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 77 publications
(64 citation statements)
references
References 39 publications
1
54
3
6
Order By: Relevance
“…Contrary to a previous report that migration leads to increase in population size (19), the mean subpopulation and metapopulation sizes of CMs in our study were significantly higher than those of LMMs or HMMs (Fig. 1C).…”
contrasting
confidence: 99%
See 3 more Smart Citations
“…Contrary to a previous report that migration leads to increase in population size (19), the mean subpopulation and metapopulation sizes of CMs in our study were significantly higher than those of LMMs or HMMs (Fig. 1C).…”
contrasting
confidence: 99%
“…Thus, rigorous tests of theoretical predictions regarding the effects of migration rate on metapopulation dynamics are rare (13). Similarly, despite a large corpus of theoretical studies (16-18), the effects of migration rates on mean population size have rarely been investigated experimentally (19).Here, we report the effects of low (10%) and high (30%) migration rates on the dynamics of replicated laboratory metapopulations of the fruit fly Drosophila melanogaster in a 21-generation experiment (20). We quantified constancy stability (21) of the metapopulations and subpopulations with the use of a dimensionless measure of amplitude of fluctuation in population size over time (22).…”
mentioning
confidence: 97%
See 2 more Smart Citations
“…Ives et al (2004) have shown that when negative density dependence is weak, migration can increase population size if immigration rate is positive when populations are growing and negative when they are declining, even when migration leads to no net additions or removals from a population. This is because migration acts to average population densities between patches.…”
Section: Migrationmentioning
confidence: 99%